From Dissent to Democracy : The Promise and Perils of Civil Resistance Transitions - Pinckney, Jonathan C. (New York Oxford University Press, 2020)
"Under what conditions will successful nonviolent revolutions lead to democratization? While the scholarly literature has shown that nonviolent resistance has a positive effect on a country's level of democracy, little research to date has disaggregated this population to explain which cases of successful nonviolent resistance lead to democracy and which do not. This book presents a theory of democratization in transitions initiated by nonviolent resistance based on the successful resolution of two central strategic challenges: maintaining high transitional mobilization and avoiding institutionally destructive maximalism. I test the theory first on a dataset of every transition from authoritarian rule in the post-World War II period and second with three in-depth case studies informed by interviews with key decision-makers in Nepal, Zambia, and Brazil. The testing supports the importance of high mobilization and low maximalism. Both have strong, consistent effects on democratization after nonviolent resistance
Include Illustrations, Maps, Graphs and Index
Keywords: Democratization. -- Civil disobedience. -- Democratization -- Nepal. -- Zambia